Mechanical characterization of unsaturated polyester composite filled modified kenaf fiber / Suzana Ratim, Rahmah Mohamed and Siti Norasmah Surip - Ratim, Suzana; Mohamed, Rahmah; Surip, Siti Norasmah (Research Management Institute (RMI), 2012)
Lignecellulosic fibers such as jute, ramie, kenaf, coir have attracted consideration as alternative materials to replace synthetic fiber and other conventional reinforcements. These natural fiber composite combine good mechanical properties with low specific mass ad offer alternative materials for glass fiber reinforced plastics in some technical application (Gassan 2002). Despite the attractiveness of natural fiber reinforced polymer matrix composites, they suffer from lower modulus, lower strength and relatively poor moisture resistance compared to synthetic fiber reinforced composites (Thwe and Liao, 2002). One difficulty that has prevented the use of natural fibers is the lack of good adhesion with polymeric matrices (Bessadok et al. 2008). According to Gassan 2002, their high level of moisture absorption, poor wettability by non-polar plastic and insufficient adhesion between untreated fibers and polymer matrix lead to debonding with age. The presence of hydroxyl and other polar groups in natural fiber, moisture uptake can lead to weak interfacial bonding between the fibers and hydrophobic polymer matrices (Thwe and Liao, 2002). In particular, the great moisture sorption of natural fibres adversely affects adhesion with hydrophobic matrix leading to premature ageing by degradation and loss of strength reactions (Bessadok et al. 2008). Previous study shown that degradation of mechanical properties caused by higher moisture uptake of natural fiber (Karmaker 1997). Interfacial adhesion and resistance to moisture absorption of natural-fibre composites can be improved by treating these fibres with suitable chemical reactions (Bessadok et al. 2008). It is necessary to enhance the hydrophobisity of natural fiber by chemical treatments with suitable coupling agents or coating with appropriate resin to develop better mechanical properties and environmental performance (Thwe and Liao, 2002).